ON COEFFICIENT BOUNDS AND FUNCTIONALS OF ANALYTIC FUNCTIONS ON A UNIT DISC - Ajai, Philip Terwase; Opoola, T. O.; Babalola, K. O. (FUDMA JOURNAL OF SCIENCES, 2021)
We introduce and investigate a new subclasses of the function class of biunivalent functions defined in the open unit disk, which are associated with linear combinations of some geometric expressions, satisfying subordinate conditions. Coefficients and Fekete-Szegö functional for the class are obtained.
Keywords: Analytic functions, univalent functions, subordination, Hadamard product, linear combination